2014
DOI: 10.1002/dmrr.2491
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus with normal renal function is associated with anaemia

Abstract: Anaemia is more common in diabetic patients even when eGFR > 60 mL/min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
3
23
0
2
Order By: Relevance
“…Of note, in the 50-to 64-year-old group the prevalence in men rises to 4.4% and the women's rates drop by half to 6.8% [16]. Our finding of 4.4% prevalence is also consistent with a recent cohort study of about 30,000 Swedish participants aged 44-73 which showed a prevalence of anemia of 3.8% [3], and a small Israeli cohort of similar subjects who attended a periodic medical examination clinic and had a prevalence of anemia of 2.7%, in non-diabetics [17]. Data regarding longitudinal assessment of anemia development in the general population are lacking in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…Of note, in the 50-to 64-year-old group the prevalence in men rises to 4.4% and the women's rates drop by half to 6.8% [16]. Our finding of 4.4% prevalence is also consistent with a recent cohort study of about 30,000 Swedish participants aged 44-73 which showed a prevalence of anemia of 3.8% [3], and a small Israeli cohort of similar subjects who attended a periodic medical examination clinic and had a prevalence of anemia of 2.7%, in non-diabetics [17]. Data regarding longitudinal assessment of anemia development in the general population are lacking in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…The National Kidney Foundation's clinical practice guidelines define anemia as a hemoglobin (Hb) concentration lower than 13.5 g/dL for adult men and less than 12.0 g/dL for adult women [14]. However, anemia develops earlier in the course of CKD among patients with DM [15][16][17] and the severity of anemia tends to be more marked in these patients compared to nondiabetic subjects, regardless of the stage of CKD, while this difference is even most prominent among CKD stage 3 patients [18][19][20][21]. Several studies have demonstrated the importance of early detection of anemia in patients with T1DM and T2DM [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In Current Topics in Anemiathe cohort of >9000 patients without renal disease, DM was an independent determinant of Hb levels [24]. Many factors have been suggested additionally contributing to the pathogenesis of anemia in DM patients, such as erythropoietin deficiency due to efferent sympathetic denervation of the kidney in diabetic neuropathy, chronic inflammatory reaction leading to functional iron deficiency, non-selective urinary protein excretion leading to transferrin and erythropoietin loss and the use of RAAS blockers [5,25].…”
Section: Anemia In Chronic Kidney Diseasementioning
confidence: 99%
“…Anemia has been found in about 10% of DM patients with normal kidney function [24]. In Current Topics in Anemiathe cohort of >9000 patients without renal disease, DM was an independent determinant of Hb levels [24].…”
Section: Anemia In Chronic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation